2023
DOI: 10.3390/ma16062530
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Abrasive Wear Behaviour of Hybrid High-Boron Multi-Component Alloys: Effect of Boron and Carbon Contents by the Factorial Design Method

Abstract: This paper is devoted to the evaluation of the “three-body-abrasion” wear behaviour of (wt.%) 5W–5Mo–5V–10Cr-2.5Ti-Fe (balance) multi-component (C + B)-added alloys in the as-cast condition. The carbon (0.3 wt.%, 0.7 wt.%, 1.1 wt.%) and boron (1.5 wt.%, 2.5 wt.%, 3.5 wt.%) contents were selected using a full factorial (32) design method. The alloys had a near-eutectic (at 1.5 wt.% B) or hyper-eutectic (at 2.5–3.5 wt.% B) structure. The structural micro-constituents were (in different combinations): (a) (W, Mo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Yang et al [25] researched the corrosion and mechanical behavior of the as-cast and solid-solution-treated AM50 magnesium alloy in different media. Chabak et al [26] investigated the abrasive wear behavior of hybrid high-boron multi-component alloys, including the effect of boron and carbon contents, employing the factorial design method. Purba et al [27] studied the three-body abrasive wear resistance of 5V/5Nb-5Cr-5Mo-5W-5Co-Fe multicomponent cast alloys with different carbon percentages.…”
Section: Contributionsmentioning
confidence: 99%
“…Yang et al [25] researched the corrosion and mechanical behavior of the as-cast and solid-solution-treated AM50 magnesium alloy in different media. Chabak et al [26] investigated the abrasive wear behavior of hybrid high-boron multi-component alloys, including the effect of boron and carbon contents, employing the factorial design method. Purba et al [27] studied the three-body abrasive wear resistance of 5V/5Nb-5Cr-5Mo-5W-5Co-Fe multicomponent cast alloys with different carbon percentages.…”
Section: Contributionsmentioning
confidence: 99%
“…Meanwhile, it is important to investigate the wear performance of these new cast alloys as the main goal of material development. Indeed, the wear behavior of HMCAs in as-cast condition under abrasion test has been initiated in the recent research of Chabak et al [30]. It has been revealed that the increment of eutectic carborides provides better wear performance.…”
Section: Introductionmentioning
confidence: 99%